European evangelicals in Egypt (1900-1956) : cultural entanglements and missionary spaces - Boulos, Samir. (Studies in Christian Mission, 2016)
Missionary institutions were social spaces of closest encounters between Europeans and various segments of the Egyptian society, during the period of British colonialism. In European Evangelicals in Egypt (1900-1956) Samir Boulos develops a theory of cultural exchange that is based on the examination of interactions, experiences and discourses in the context of missionary institutions. Drawing upon oral history interviews as well as rich Egyptian, British and German archival sources, a multifaceted perspective is offered, revealing the complexity and dynamics of mission encounters. Focusing on the everyday life in missionary institutions, experiences of former Egyptian missionary students, local employees, as well as of European missionaries, Samir Boulos explores mutual transformation processes particularly on the individual but also on institutional and social level.